KATA BILANGAN BAHASA KAIS RAGAM AWE DI DISTRIK KAIS KABUPATEN SORONG SELATAN - Agustinus G Gifelem (Yayasan Akrab Pekanbaru, 2019)
This study aims to analyze the Kais language numbers of the Awe variety found in the Strait district of Sorong which is located in the Kais District region. Data were analyzed using a qualitative approach. Based on the analysis carried out, it was found Kais Variety Awe language has a number of words that vary based on the raw data obtained, so the data is classified based on Alwin's theoretical framework so that it can be clearly determined that in Kais language there are a number of Awe, there are number words including principal number Of course the basic number words, collective principal number words, distributife number words, fixed principal numbers) and level number words (phrase number words).